Leaders, groups and influence - "Hollander, E.P." (New York, 1964)
Preface In the social psychology of the 1960's, many viewpoints compete for the key to social influence. Under diverse hcadings, and in dis- tinctive ways, lines of activity are pursued which speak question of how one person's action is affected by others. 'To ac- count for this, there are discrepancy hypotheses and cognitive dissonance, thcories of interpersonal perception, and measures of social desirability, dogmatism, and conformity. But, whatever their emphasis, all bear upon this central phenomenon. Leadership is one avenue by which to approach social influence. It, too, has its distinguishing attributes. Some years ago in studying emergent leadership through sociometric procedures, I became es- pecially interested in the basis for the assessments made. Further research indicated that quite separable categories of source were involved and that respondents could readily differentiate among these. The results suggested that, within various group settings, a kind of implicit interpersonal assessment was at work in several dimensions, among which are: perceived competence, in the sense of moving the group toward a valued goal; perceived conformity, in terms of living up to applicable group expectancies; and char- acteristics perceived as valued for their own sake.
Keywords: Sociology